2023
DOI: 10.1108/jmp-03-2022-0124
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the limits of mindfulness during the COVID-19 pandemic: qualitative evidence from African context

Abstract: PurposeThis paper is one of the first studies to examine specificities, including limits of mindfulness at work in an African organisational context, whilst dealing with the ongoing COVID-19 pandemic. It specifically addresses the role of organisational and managerial support systems in restoring employee wellbeing, social connectedness and attachment to their organisations, in order to overcome the exclusion caused by the ongoing pandemic.Design/methodology/approachThe study uses a qualitative research method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 134 publications
0
11
0
Order By: Relevance
“…In the context of a virtual workplace where supervisors employ abusive tactics, the employees may find themselves lacking the necessary resources to cope with the stressful conditions (Zhang et al, 2019). Furthermore, abusive supervision during forced teleworking heightens employees' ambiguity and uncertainty surrounding COVID-19 (Wang et al, 2022), which in turn triggers anxiety and insecurity, hindering employees' ability to remain present in the moment (Alo et al, 2023;Zheng et al, 2022). Consequently, employees experience resource depletion due to abusive supervision in the context of COVID-19.…”
Section: Abusive Supervision and State Mindfulnessmentioning
confidence: 99%
See 1 more Smart Citation
“…In the context of a virtual workplace where supervisors employ abusive tactics, the employees may find themselves lacking the necessary resources to cope with the stressful conditions (Zhang et al, 2019). Furthermore, abusive supervision during forced teleworking heightens employees' ambiguity and uncertainty surrounding COVID-19 (Wang et al, 2022), which in turn triggers anxiety and insecurity, hindering employees' ability to remain present in the moment (Alo et al, 2023;Zheng et al, 2022). Consequently, employees experience resource depletion due to abusive supervision in the context of COVID-19.…”
Section: Abusive Supervision and State Mindfulnessmentioning
confidence: 99%
“…However, these studies have often overlooked the significant role of mindfulness, an essential personal resource (Du et al ., 2019; Orazi et al ., 2021). During the COVID-19 period, mindfulness has emerged as a crucial tool for managing negative emotions and depression (Alo et al ., 2023; Lam et al ., 2022). State mindfulness, in particular, is characterized by non-judgmental metacognitive monitoring in the present moment, free from attachment to the past or future.…”
Section: Introductionmentioning
confidence: 99%
“…The last article by Alo et al (2024), "Exploring the limits of mindfulness during the COVID-19 pandemic: qualitative evidence from African context," explores the linkage between the COVID-19 pandemic and the boundaries of mindfulness in an African organizational work setting. They found that the pandemic-induced worries during its peak limit the practice of mindfulness, mainly due to the worsening already harsh economic conditions, social uncertainties and institutional challenges in Africa.…”
Section: Guest Editorialmentioning
confidence: 99%
“…The last article by Alo et al . (2024), “Exploring the limits of mindfulness during the COVID-19 pandemic: qualitative evidence from African context,” explores the linkage between the COVID-19 pandemic and the boundaries of mindfulness in an African organizational work setting.…”
Section: This Special Issuementioning
confidence: 99%
See 1 more Smart Citation